Design and development of three stages maximum power tracking solar charge controller - N.H. Abdul Rahman; A. M. Omar; E. H. Mat Saat; N. I. Ilham; M. Z. Hussin; Yusrina Y (Institute of Advanced Engineering and Science, 2020)
This paper presents the design of a Three Stages Maximum Power Point Tracking (MPPT) charge controller for improving the charging/discharging control of the battery. In this research, Buck Converter is used to regulate the voltage from the Photovoltaic (PV) module to the required voltage. This research is limited to Valve Regulated Lead Acid (VRLA) battery for 12V system voltage. The charge control algorithm envisages controlling the charging and discharging action in all the three stages of battery charging, bulk, absorption, and float. The idea is to control the battery charging and discharging status until meeting the battery set-point. The set-point is limited to High Voltage Disconnect (HVD), Low Voltage Disconnect (LVD) and Load Voltage Reconnect (LVR) to protect the battery from over-charging and deep-discharging. The results obtained demonstrate the good performance of the charge controller. With the application of the MPPT algorithm in the bulk stage, the time taken to get the battery to fully charged state becomes faster The regulation power from the converter to the inverter has performed well and the switching relay is managed to be controlled.